CHALLENGES AND OPPORTUNITIES OF ISLAMIC EDUCATION IN PREPARING A RESILIENT GENERATION IN ERA 5.0 - Mahfud Heru Fatoni; Sukari; Lee Hoang Nam (Yayasan Adra Karima Hubbi, 2026)
The end of the industrial revolution era with various changes, society is forced to enter the 5.0 era. Various innovations have emerged and require the ability to adapt. This study aims to reveal the challenges and opportunities of Islamic education in preparing a strong generation in the 5.0 era. This study uses a literature study method often referred to as a Scoping review. The author identifies various literatures that use various methods with themes related to the topic of challenges and opportunities for Islamic education in facing society 5.0. The results of the study show that the problems that emerge as challenges to Islamic education are: moral decadence, the emergence of non-educational media that are easily consumed by children, inappropriate use of social media, situations that demand to compete in various aspects, the necessity of democracy and modern developments, demands to survive the crisis and maintain what has been achieved, demands to compete both on a regional, national and international scale, demands to adapt to rapid changes. To anticipate these challenges, namely by fostering religious understanding to hone spiritual and emotional intelligence, creating as much useful content as possible that is in accordance with Islamic teachings using various media that are easily consumed by all groups, strengthening Islamic education that focuses on character development in children, providing 21st century skills to survive the demands of democracy and modernization, preparing reliable educators who are able to carry out renewal and have a forward-looking orientation.